Peningkatan Kualitas Sumber Daya Manusia Melalui Program Kuliah Kerja Mahasiswa di Desa Pagedangan, Kecamatan Turen - Hariyono, Ahmad; Supriyanto, Supriyanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The Highest Educations is one of the elements of the country which is expected to be able to realize the nation's ideals to elevate the dignity of the Indonesian nation. There are three points in the Tri Dharma of Highest Educations, namely: Education, Research and Community Service. Student Work Lecture (KKM) activities are based on social interactions involving various elements of society. It is hoped that this activity will be beneficial for the local community, while also requiring students to provide long-term solutions so as to reduce similar problems. In implementing KKM, research is carried out through data collection techniques from observation and documentation of social situations, where the data is obtained in exploration activities in the community environment and the impact of the KKM program provided on the community. Based on data analysis, the technique used is analysis with a descriptive approach through the data obtained, then processed based on research objectives and then filtered based on situations and phenomena in society with similar data contexts. As a result, a number of programs were carried out in accordance with community needs, such as: qiraah training, creating of reading corners, learning media, etc. It is hoped that this activity will be useful for development and empowerment in accordance with community potential.